Edukasi dan Sosialisasi Cybercrime terhadap Keamanan Data bagi Kelompok Pembina Kesejahteraan Keluarga - Karim, Abdul; Biharudin, Akmal; Hidayat, Ahmad Rian; Arifin, Muhammad Syamsul (Insan Kreasi Media, 2023)
Cybercrime poses a serious challenge in the digital era, threatening data security and digital infrastructure. The PKK Group in Alassumur Lor Village, consisting of mothers, is vulnerable to cyberattacks due to a lack of technological understanding. They encounter difficulties in using devices, lack digital security awareness, and have minimal knowledge of privacy. To address this, an approach focusing on enhancing technological literacy through training is essential to comprehend and tackle daily technical issues. The engagement with the PKK Group in Alassumur Village emphasizes education and awareness about cybercrime and the importance of data protection. Workshops, group discussions, and material creation are utilized to raise awareness about cyber security. The goal is to instigate behavioral changes, the emergence of local leaders, and the formation of new cadres within the group, thereby strengthening collective data protection. The outcomes demonstrate positive changes in data security practices, understanding of cybercrime risks, and the emergence of leaders and new cadres. Recommendations include continuous cybercrime education, the use of social media for communication, and periodic evaluations to measure impact. The hope is for awareness about cybercrime and data protection to continue growing, becoming a part of societal culture, and safeguarding against future cyber threats.